Novel amperometric gas sensors - Wallgrén, Kirsi (2005)
The electrochemistry of oxygen and methanol at solid polymer electrolyte (SPE)-based amperometric sensors, fabricated according to an all-planar design concept, has been investigated. The solid protonic conductors used were Nafion®-117 membranes and Polybenzimidazole (PBI) films. The working and counter electrodes were non-porous gold and/or platinum layers (300-1500 nm thick), sputtered on the same face of the solid electrolyte, separated by a gap of the ionic conductor (10-1 mm wide) and in contact with the gas sample. Such all-planar solid-state devices could offer potential advantages over sandwich-type gas sensors namely, reduction in precious metal electrode area and simplified fabrication.